Ultra-tough light-curing ionogels for UV shielding - Zeyu Zhang; Dejun Peng; Xueyan Shang; Xin Zhao; Shixue Ren; Jiuyin Pang; Shujun Li (Communications Materials)
Abstract The mechanical properties of polyurethane ionogels prepared by UV light-curing are usually inferior to those of conventional polyurethanes. Highly entangled polymer chain networks with chemical crosslinking can potentially address this problem. Here, we prepare ionogels (PU-HRs) using UV curing technology with esterified rutin as a cross-linking agent. After optimization of the preparation process by response surface methodology, we obtain PU-HRs with a tensile strength of 34.96 MPa and toughness as high as 88.11 MJ m−3 (1.26-fold higher than that of silk from the silkworm, Bombyx mori (70 MJ m−3)). The high strength and toughness of PU-HR are mainly attributed to the three-dimensional cross-linked network structure formed by the “rigid-flexible” esterified rutin, the micro-phase separation structure between the soft-chain fragments, and the hard-chain fragments that form stable interfacial regions. These ionogels have great prospects in sunscreen coating applications, such as for sunscreen umbrellas and automotive or architectural sunscreen glass.